Experimental study of fast-neutron production and moderation for accelerator-based BNCT system. (October 2019) - Koay, H.W.; Shima, T.; Fukuda, M.; Kanda, H.; Hara, S.; Yorita, T.
Abstract: This work aims to study the fast-neutron production and moderation for the development of a compact accelerator-based multi-port Boron Neutron Capture Therapy (AB-mBNCT) system. An initial energy distribution and the efficiency of a test moderator assembly (TMA) for fast neutrons from a tungsten (W) target bombarded with a 53 MeV proton beam were measured using organic scintillators. The experimental results were reproduced with reasonable accuracy by simulations using the PHITS code. This paper will discuss about the experimental outcome and the related benchmark calculations by PHITS code. Highlights: The angular neutron spectra from Bertini + GEM model shows good agreement with the experimental results for E < 40 MeV. INCL + GEM model overestimated the integrated yield within 20–23% for all angles. Similar moderation tendency was seen between simulated and experimental data within average percentage difference of 36%.